Анализ путей модернизации тягового двигателя постоянного тока ДТН-45/27, предназначенного для привода рудничного контактного электровоза - Шайда, Виктор Петрович; Юрьева, Елена Юрьевна; Гринь, Д. А. (НТУ "ХПИ", 2016)
Проведен сравнительный анализ параметров и конструкций тяговых двигателей постоянного тока. Выявлены технические решения, позволяющие повысить технико-экономические показатели тягового двигателя. Выявлены преимущества и недостатки в конструкции и технологии производства тяговых двигателей постоянного тока. Предложен способ увеличения почасовой мощности двигателя постоянного тока типа ДТН-45/27. Предложены конструктивные решения, которые повышают надежность двигателя при эксплуатации в шахте.

A comparative analysis of parameters and designs DC traction motors to identify technical solutions aimed at improving the technical and economic indicators. Methodology. On the basis of the comparative analysis revealed strengths and weaknesses in the design and manufacture technology of traction motors DC. Results. The situation was considered in the operation of technological transport of iron ore mines at the present time. The main directions of modernization of contact electric locomotive for mines especially K14 were identified. The analysis of the structure and parameters traction motor DC type DTН-45/27 and its analogs were done. A way to increase the hourly power traction motor DC type DST-45/2 was proposed. Originality. The novelty of the results was achieved by integration of the design and manufacture technology of traction motors DC type DТН-45/27. Practical value. Ways of increasing the power of traction motors DC in long-term and short-term work were proposed. We support the method of control, motor monitoring and protection against overheating.
Analysis of ways to modernize the traction motor DC DTН-45/27 for the drive of miner contact electric locomotive
Keywords: электрические машины; часовая мощность; класс нагревостойкости изоляции; вакуум-нагнетательная пропитка якоря; конструктивные решения; надежность двигателя; miner contact electric locomotive; traction motor DC; hourly power; insulation system; vacuum-injection steep armature